2011
DOI: 10.1007/s10151-011-0719-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoanal ultrasonography may distinguish Crohn’s anal fistulae from cryptoglandular fistulae in patients with Crohn’s disease: a cross-sectional study

Abstract: Endoanal ultrasonography was capable of discerning two subgroups of fistula in Crohn's patients. These groups were clinically different indicating that the prospect of surgical cure is also different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…One is the so-called Crohn's Ultrasound Fistula Sign (CUFS) consisting of a hypoechoic rim around an abscess collection or fistula and a hyperechoic margin alongside, presumably indicative of a chronic inflammatory process [26]. Further data from Blom et al [27] have suggested that CD-related anal fistulae are more likely than cryptogenic fistulae to be bifid or to contain intra-fistula debris and tend on average to be wider in diameter than their cryptogenic counterparts. Recent data from Zbar et al [28] suggests that the CUFS is only moderately sensitive but is highly specific for the diagnosis of PACD in a first perianal presentation, although the other fistula signs as described by Blom et al appear to be less discriminatory.…”
Section: Discussionmentioning
confidence: 96%
“…One is the so-called Crohn's Ultrasound Fistula Sign (CUFS) consisting of a hypoechoic rim around an abscess collection or fistula and a hyperechoic margin alongside, presumably indicative of a chronic inflammatory process [26]. Further data from Blom et al [27] have suggested that CD-related anal fistulae are more likely than cryptogenic fistulae to be bifid or to contain intra-fistula debris and tend on average to be wider in diameter than their cryptogenic counterparts. Recent data from Zbar et al [28] suggests that the CUFS is only moderately sensitive but is highly specific for the diagnosis of PACD in a first perianal presentation, although the other fistula signs as described by Blom et al appear to be less discriminatory.…”
Section: Discussionmentioning
confidence: 96%
“…At present, we do not know the histological explanation of CUFS, but we speculate that this might be due to a deep inflammatory process associated with Crohn’s fistula, with the hyperechoic component of CUFS being a reflection of inflammatory debris although its actual nature needs to be examined in future studies. A recent study reported that Crohn’s fistula might be characterised by the presence of bifurcations and a track wider than 3 mm although the prevalence of these findings in cryptoglandular fistulas was not determined [19].…”
Section: Discussionmentioning
confidence: 99%
“…An endosonographic classification of perianal Crohn's disease has been developed, which in a large series led to a change in management in just under half of the 150 cases reviewed . The endosonographic differences in appearances between Crohn's fistulas and cryptogenic sepsis have been detailed, with wider branched tracks and the presence of debris typical in Crohn's fistulas . The mean greyscale of a track on endosonography may also be positively correlated with the perianal Crohn's disease activity index and assessment of fistula drainage in Crohn's disease .…”
Section: Imagingmentioning
confidence: 99%